The Effectiveness of Digital Storytelling at Increasing Learning Motivation in Early Childhood from the Female Teachers' Point of View - Alshahrani, Haya Saud (Journal of Curriculum and Teaching Methodology, 2024)
This study is aimed at identifying the effectiveness of digital storytelling at increasing learning motivation in early childhood from the point of view of teachers. The study sample consisted of (458) early childhood female teachers in Riyadh region. The study tools included a questionnaire about the effectiveness of digital storytelling at increasing learning motivation in early childhood from the teachers' point of view. After applying the study tools and using statistical methods, the study reached the following results: There are statistically significant differences at the level of (0.05) and that the study sample members agree on (the effectiveness of the digital stories at increasing the motivation for early childhood learning) with percentage of (92.60%), and a general arithmetic mean of (4.63 out of 5), that falls in a strongly agreeable category as it is between (4.21 to 5.00). It was also found that there are some obstacles that prevent the application of the use of digital storytelling in early childhood from the female teachers’ point of view, some of which are represented at the weak skills of female teachers at the production of digital stories, followed by the lack of stories that support the curricula approved by the Ministry. The study recommended the necessity of training female teachers to produce digital stories, as well as developing official plans through the Ministry of Education to produce stories and develop appropriate plans for teaching through them.
Keywords: Digital Stories; Motivation Towards Learning; Early Childhood Stage